Nitric Oxide Synthase as a Target for Methicillin-Resistant Staphylococcus aureus. Issue 6 (18th June 2015) - Holden, Jeffrey K.; Kang, Soosung; Beasley, Federico C.; Cinelli, Maris A.; Li, Huiying; Roy, Saurabh G.; Dejam, Dillon; Edinger, Aimee L.; Nizet, Victor; Silverman, Richard B.; Poulos, Thomas L.
Summary Bacterial infections associated with methicillin-resistant Staphylococcus aureus (MRSA) are a major economic burden to hospitals, and confer high rates of morbidity and mortality among those infected. Exploitation of novel therapeutic targets is thus necessary to combat this dangerous pathogen. Here, we report on the identification and characterization, including crystal structures, of two nitric oxide synthase (NOS) inhibitors that function as antimicrobials against MRSA. These data provide the first evidence that bacterial NOS (bNOS) inhibitors can work synergistically with oxidative stress to enhance MRSA killing. Crystal structures show that each inhibitor contacts an active site Ile residue in bNOS that is Val in the mammalian NOS isoforms. Mutagenesis studies show that the additional nonpolar contacts provided by the Ile in bNOS contribute to tighter binding toward the bacterial enzyme.